Technical Efficiency of Yam Commodity in Semarang Regency - Avi Budi Setiawan; Ngatindriatun Ngatindriatun; Karsinah Karsinah (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2019)
Semarang Regency has the largest area of ​​yam harvest in Central Java. Although the area of ​​yam harvest in Semarang Regency is much more than other districts including Karanganyar Regency, the production and productivity level of yam in Semarang Regency are lower compared to Karanganyar Regency. The tendency of increasing yam harvest area in Semarang Regency was not followed by an increase in production. This study aims to analyze the efficiency of yam farming in Semarang Regency. The sample is 97 farmers with the data analysis technique is stochastic frontier regression. Based on the results, an average efficiency is 0.75. It implies that yam farmers have not been able to combine the use of land area, seeds, urea, SP-36 and phonska. The results of price efficiency is 19.233. The results of these calculations indicate that the use of production factors in yam has not efficiency. Farmers can optimize the use of production factors by adding production factors. The level of economic efficiency is 14.433, it indicate that the use of production factors has not been efficient based on economic aspects, because the calculation results is more than 1.